FACTORS INFLUENCING MEDICAL STUDENTS’ CHOICE FOR FAMILY MEDICINE AS A SPECIALTY IN PAKISTAN - Ehsan, Sumera Badar; Hasnain, Musarrat ul (Journal of Ayub Medical College Abbottabad, 2018)
Background: Multiple factors influence career selection for medical students. In developed countries, training in family medicine is essential to start practice as a general practitioner. In Pakistan this specialty was introduced by College of Physicians and Surgeons Pakistan in 90’s but it has not been yet institutionalized. This study was conducted to identify the factors that influence students’ choice for Family medicine as a specialty. Methods: It was a sequential (quantitative first) mix method study which was conducted in two medical colleges (one public sector and other private) of Faisalabad from April to June 2014. In first phase students’ career choices were determined in a sample of 252 students. In second phase 12 students were selected randomly for interviews; six students who selected family medicine as a specialty and six students who had selected some other specialty. In depth interviews and focused group discussion were used to explore the factors that influenced them for selecting the respective specialty. Results: Major factor for not selecting family medicine was lack of awareness about the scope of specialty. Other factors included personal interest, feasibility and family influence. Conclusion: Lack of awareness and scope of family medicine is the predominant factor in influencing students for choosing family medicine as a career. Career counselling, role modelling and exposure to this specialty during clinical years can play an important role in promotion of this field. Keywords: Family medicine; career choice; medical students; career counselling